2019
DOI: 10.1002/prep.201900164
|View full text |Cite
|
Sign up to set email alerts
|

Detonation Characteristics of an Aluminized Explosive Added with Boron and Magnesium Hydride

Abstract: Investigation of the detonation characteristics of an aluminized explosive added with boron (B) and magnesium hydride (MgH 2 ) were undertaken and compared with the aluminized explosive of similar formulation. Firstly, the explosion heat was measured in a vacuumed calorimetric bomb, then the detonation pressure was determined by the interface velocity experiment, and finally the cylinder expansion test was performed. From the calorimetric data, the addition of B and MgH 2 into an aluminized explosive increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Recently (2019), it has been proposed that magnesium hydride be used as a boron activator; however, the addition of these two fuels deteriorates the blast effect compared with the addition of standard aluminized explosive. Only the heat of detonation increased slightly (by about 1.5 %) [10].…”
Section: Introductionmentioning
confidence: 93%
“…Recently (2019), it has been proposed that magnesium hydride be used as a boron activator; however, the addition of these two fuels deteriorates the blast effect compared with the addition of standard aluminized explosive. Only the heat of detonation increased slightly (by about 1.5 %) [10].…”
Section: Introductionmentioning
confidence: 93%
“…W. Cao et al. [11] found that the combustion heat of metallic explosives enhanced with the increasing content of boron powder within certain limits.…”
Section: Introductionmentioning
confidence: 99%
“…E. C. Koch et al [10] studied the detonation velocities and pressures of the boron-based high explosives, and discovered that the detonation velocities of the boron-based compounds were always higher than that of the corresponding carbon-based compounds. W. Cao et al [11] found that the combustion heat of metallic explosives enhanced with the increasing content of boron powder within certain limits.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminized explosives have been widely used in ammunitions due to their high blast and incendiary effects [1]. The aluminum powders in explosives react with detonation products and environmental gases to release large amounts of heat, which increases the heat of detonation and damage to the target [2][3][4]. On the one hand, higher performance has always been a prime requirement in the field of research and development of explosives and the quest for the most powerful high explosives still continues and never ends.…”
Section: Introductionmentioning
confidence: 99%
“…TATB (2,4,6-triamino-1,3,5-trinitrobenzene, C 6 H 6 N 6 O 6 ) is a reasonably powerful high explosive (HE) whose thermal and shock stability is considerably greater than that of any other known material of comparable energy [6]. TATB-based aluminized explosives have exhibited the highly thermal stability, and high detonation performance [7].…”
Section: Introductionmentioning
confidence: 99%